MENA SMEs: Assessing Barriers and Enablers of Technological Adoption - Al Khalifa, Muneera M. (Journal of Ecohumanism, 2025)
Small and Medium-Sized Enterprises (SMEs) in the Middle East and North Africa (MENA) are critical drivers of economic diversification and employment. However, these enterprises often face significant challenges in adopting digital technologies, hindering their growth and competitiveness. This study employs a mixed-methods approach, integrating quantitative surveys of 400 SMEs across five MENA countries—Egypt, Jordan, Morocco, Saudi Arabia, and the United Arab Emirates—and qualitative interviews with 35 stakeholders, including SME owners, policymakers, and technology providers. The research identifies key barriers such as limited access to finance, inadequate digital infrastructure, regulatory fragmentation, and cultural resistance. Conversely, enablers include government incentives, managerial digital literacy, capacity-building programs, and cross-sector collaborations exemplified by initiatives like Abbott’s (2023) telehealth partnerships. Comparative analysis of Southeast Asia and Sub-Saharan Africa highlights the best practices and contextual nuances. The findings offer actionable policy recommendations aimed at enhancing financing mechanisms, harmonizing regulatory frameworks, upgrading digital infrastructure, and fostering managerial competencies. By addressing these factors, MENA SMEs can effectively integrate digital solutions, thereby promoting sustainable economic development and enhancing regional competitiveness.